Hippocampus sparing volumetric modulated arc therapy in patients with loco-regionally advanced oropharyngeal cancer. (October 2022) - Seol, Seung Won; Lee, Brian H.; Sita, Timothy L.; Devineni, Jay Ram; Kruser, Tim J.; Sachdev, Sean; Gentile, Michelle; Helenowski, Irene; Mittal, Bharat B.
Abstract: This study aimed to assess the incidental radiation exposure of the hippocampus (HC) in locoregionally-advanced oropharyngeal cancer patients undergoing volumetric modulated arc therapy and the feasibility of HC-sparing plan optimization. The initial plans were generated without dose-volume constraints to the HC and were compared with the HC-sparing plans. The incidental Dmean _median doses to the bilateral, ipsilateral and contralateral HC were 2.9, 3.1, and 2.5 Gy in the initial plans and 1.4, 1.6, and 1.3 Gy with HC-sparing. It was feasible to reduce the HC dose with HC-sparing plan optimization without compromising target coverage and/or dose constraints to other OARs.